HUBUNGAN INDEKS PRESTASI KOMULATIF (IPK) DAN LAMA STUDI TERHADAP NILAI UJIAN KOMPREHENSIF MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA - Rahmat, Tasnim; Medika, Gema Hista (Math Educa Journal, 2023)
This study aims to see whether there is a relationship between the Grade Point Average (GPA) and length of study to comprehensive exam scores. This research is descriptive quantitative research. The population of this research is graduated students of the mathematics education study program at IAIN Bukittinggi for the last 4 years; students who have graduated in 2018, 2019, 2020, 2021, consisting of 353 people. The sample was 15% of 353 people (53 people). The data analysis technique was statistical analysis in which the step started by firstly carrying out the prerequisite analysis test. Next, the hypothesis test is carried out. The results showed that the results of the first correlation test that had been carried out had a relationship between the Grade Point Average and the student's comprehensive score. From data analysis through correlation analysis, it obtained 0.318 with a coefficient of determination of 10.112%. It means that there is a relationship between the Grade Point Average and the student's comprehensive score. This shows that the relationship between GPA and the compressive score is positive even though it is weak. The second correlation test which was carried out did not show any relationship between the length of study and the student's comprehensive score. From the analysis of the data through correlation analysis, it was obtained -0.278 which indicated that the relationship between the length of study and the compression value had a negative score and had weak relationship strength. Based on the third hypothesis test that has been carried out there is no relationship between the Grade Point Average (GPA) and the length of study with the student's comprehensive score.